Peer Counselor-Based Mental Health Development At The Tahfidzul Qur'an Muhammadiyah Srumbung Islamic Boarding School - Tahmid Miftachurrozaq; Arif Rahman (Ananda: Jurnal Pendidikan Anak dan Remaja, 2025)
Mental health disorders through self-harm cause situations and conditions that are not conducive in the Islamic boarding school environment, compounded by the stigma that arises in society related to this. The purpose of this study was to analyze the mental health of students who hurt themselves and how to deal effectively with mental health disorders in students. This study employed a qualitative research approach with field research. Data collection techniques include observation, interviews, and documentation. This study was analyzed through data reduction, data presentation, and a conclusion. The results of this study indicate that peer counselors' efforts to improve the mental health of students have a big influence on the students themselves. The method used in overcoming these cases is by conducting counseling between peers, also known as "peer counselors." In conducting peer counseling, there must be several stages to expedite the program. These stages include preparation, socialization, basic training, advanced training, mentoring, evaluation, and program follow-up.